Report on Evaluation of the Urban Milk Supply Schemes - Planning Commission (Planning Commission, 1974)
Milk is an important source of protein, particularly for a vegetarian population. Every quarter litre of milk supplies easily digestible proteins equivalent to 50 grains of meat or fresh fish or one and a half egg. Besides, it also supplies necessary quantities of amino-acids, mineral elements and vitamins having biological and growth promotion value for persons of all age groups. Although India had the largest cattle population in the world, productivity of milk is ono of the lowest.
Programme Evaluation Organisation Planning Commission Government of India